Changes in facial width according to the ostectomy level of the proximal bone segment in intraoral vertical ramus osteotomy for mandibular prognathism - Sang-Hoon Kang; Min-Jun Kang; Min-Ji Kim; Moon-Key Kim (SpringerOpen, 2022)
Abstract Background This study aimed to investigate the changes in facial width according to the ostectomy level of the proximal segment after orthognathic surgery using intraoral vertical ramus osteotomy (IVRO) in patients with mandibular prognathism. Methods The participants included 32 individuals who were diagnosed with class III malocclusion prior to surgery. All participants underwent orthognathic surgery using either version of IVRO. The surgery patients were categorized into two groups depending on the type of proximal bone-segment ostectomy technique used: patients whose osteotomy height was at the level of the mandibular tooth occlusal surface (the mandibular tooth surface-level group) and patients whose osteotomy height was at the level of the mandibular inferior border (the mandibular inferior border-level group). The distances between the mandibular width and soft tissue width at the height of the sigmoid notch, mandibular foramen, and alveolar bone and at the anterior-posterior location of the mandibular condyle, mandibular foramen, and coronoid process were compared between the groups. All data were compared to identify differences between preoperative and postoperative measurements. Results The postoperative change in facial soft tissue width at the intersection of the coronal plane with the coronoid process and the horizontal plane at the height of the mandibular alveolar bone in the group with osteotomy at the level of the mandibular occlusal surface differed significantly from that in the group with osteotomy at the level of the mandibular inferior border, with respective increases (mean ± SD) of 1.3 ± 3.5% and 4.7 ± 5.6%, compared to preoperative measurements (p = 0.050). Conclusions Proximal segment ostectomy at the level of the mandibular occlusal surface must be considered with regard to postoperative facial soft tissue width in vertical ramus osteotomy. Additionally, it is necessary to study the visual effect of the width of the mandible appearing small because of the posterior position of the mandible, even when the mandibular facial width is maintained.